2022
DOI: 10.1098/rspb.2022.1589
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of marsupial social organization

Abstract: It is generally believed that marsupials are more primitive than placentals mammals and mainly solitary living, representing the ancestral form of social organization of all mammals. However, field studies have observed pair and group-living in marsupial species, but no comparative study about their social evolution was ever done. Here, we describe the results of primary literature research on marsupial social organization which indicates that most species can live in pairs or groups and many show intra-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Intraspecific variation in primate social systems recently received more attention ( 8 , 22 24 ). Kappeler and Pozzi ( 1 ) already considered IVSO in understanding primate social organization, but their statistical analysis used IVSO as one possible category and not as a continuous variable [as did several other studies on different mammalian taxa ( 34 37 )].…”
Section: Discussionmentioning
confidence: 99%
“…Intraspecific variation in primate social systems recently received more attention ( 8 , 22 24 ). Kappeler and Pozzi ( 1 ) already considered IVSO in understanding primate social organization, but their statistical analysis used IVSO as one possible category and not as a continuous variable [as did several other studies on different mammalian taxa ( 34 37 )].…”
Section: Discussionmentioning
confidence: 99%
“…In Eulipotyphla it was suggested that the ancestor might have been pair living (Valomy et al, 2015). Comparative studies using modern Bayesian statistics and databases based on field studies found pair living to be the most likely ancestral form of social organization in marsupials (Qiu et al, 2022), artiodactyla (Jaeggi et al, 2020), (Olivier, 2023). Given are total number of species and in brackets the percentage of solitary species relative to all species studied.…”
Section: Evidence From Recent Comparative Studiesmentioning
confidence: 99%
“…Therefore, one can differentiate between species that are obligately solitary living (all individuals are solitary), mainly solitary living (most individuals are solitary living) and facultatively solitary living (most individuals live in pairs or groups and less than 50% solitary). Considering such variation is important in comparative studies about social evolution and can challenge previous studies that ignored variation (Dalerum, 2007; Griesser & Suzuki, 2016; Olivier et al., 2024; Qiu et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent comparative studies have shown that this is often not the case [6, 7]. These studies showed that pair-living was most likely the ancestral form of social organisation in artiodactyls [8], primates [9], and possibly in marsupials [10] and Eulipotyphla [11], indicating that solitary living is often a derived state [12]. However, we know little about the mechanisms leading to solitary living in mammals [13].…”
Section: Introductionmentioning
confidence: 99%